Orbits and individual masses of some visual binaries - Elkholy, E. A.; Elsanhoury, W. H.; Nouh, M. I. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The orbits of visual binary systems still attract the interest of many working groups in astronomy. These orbits are the most important and reliable sources of stellar masses. In the present paper, we computed the orbits and dynamical masses of some visual binaries using an independent code. Орбиты визуально-двойных систем по-прежнему вызывают интерес у многих рабочих групп по астрономии. Эти орбиты являются наиболее важными и надежными источниками звездных масс.
Keywords: Stars